2001
DOI: 10.1016/s0735-1097(01)01625-4
|View full text |Cite
|
Sign up to set email alerts
|

Electroanatomic mapping of arrhythmogenic right ventricular dysplasia

Abstract: The pathologic substrate in ARVD can be identified by spatial association of low-amplitude endocardial electrograms, reflecting replaced myocardial tissue. The ability to accurately identify the presence, location and extent of the pathologic substrate may have important diagnostic, prognostic and therapeutic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 22 publications
5
68
0
1
Order By: Relevance
“…In ARVD, however, the process is patchy and may cause inhomogeneous scarring in anatomically disparate areas. Regardless, previous data have shown that it is still possible to identify well-demarcated borders around these abnormal regions, 12 and our present study corroborates this finding.…”
Section: Verma Et Al Substrate-based Ablation Of Vt In Arvd 3213supporting
confidence: 91%
See 1 more Smart Citation
“…In ARVD, however, the process is patchy and may cause inhomogeneous scarring in anatomically disparate areas. Regardless, previous data have shown that it is still possible to identify well-demarcated borders around these abnormal regions, 12 and our present study corroborates this finding.…”
Section: Verma Et Al Substrate-based Ablation Of Vt In Arvd 3213supporting
confidence: 91%
“…1,11 Furthermore, the use of electroanatomic voltage mapping has been previously validated to correlate with areas of scar and fatty infiltration detected by magnetic resonance imaging in ARVD patients. 12 Therefore, our definition of the substrate seems to be consistent with prior published data.…”
Section: Substrate In Arvdsupporting
confidence: 88%
“…111 Genetic testing in high-probability cases has a diagnostic yield of 40% to 50%; thus, a positive test is useful, but a negative test is not. The genes underlying ARVC are characterized by considerable natural variability, making a variant of unknown significance a common outcome of genetic testing, further emphasizing the need for careful phenotyping.…”
Section: Modi and Krahnmentioning
confidence: 99%
“…14 Three-dimensional electroanatomic voltage mapping has been recently demonstrated to accurately identify the presence, location, and extent of the pathological substrate of ARVC/D by detection of low-voltage regions that reflect RV fibrofatty myocardial atrophy. 18 The present study was designed to test whether characterization of the RV wall by electroanatomic voltage mapping increases the accuracy for diagnosing ARVC/D in a consecutive series of patients fulfilling noninvasive Task Force criteria.…”
mentioning
confidence: 99%